Bibliometric visualisation of student knowledge and skills in key literacy domains (Educational Dimension, 2024)
This study utilised bibliometric visualisation of keywords used to represent documents on reading literacy, scientific literacy, and mathematical literacy indexed in the Scopus database to analyse the volume and growth of the literature. The study adopted a bibliometric research design, an approach that is also quantitative. Data was collected from Scopus, and analysis was based on Scopus' built analytical facility while mapping was carried out using VOSViewer. Reading literacy is the youngest of the three literacies, with early references dating back to 1607. However, research on reading literacy began to gain momentum in 2002. Mathematical literacy is the oldest, but significant growth occurred around 2003, while scientific literacy dates back to 1963. The trend in publications shows the highest growth for reading literacy and the lowest for mathematical literacy. Analysing document types revealed that scientific literacy had the largest quantity of documents, while reading literacy had a higher proportion of articles compared to the other two literacies. The study provides valuable insights into the historical development and current trends within these literacy domains, shedding light on their changing dynamics and challenges.
Keywords: measuring student knowledge and skills; bibliometric visualisation; reading literacy; mathematical literacy; scientific literacy